Dinamika Kelompok Tani dalam Mendukung Pengembangan Klaster Kopi di Kabupaten Bondowoso - Djoko Soejono; Dimas Bastara Zahroza (Jurnal KIRANA, 2020)
The research objective was to determine the coffee farmers’ group dynamics and the coaching partern of coffee farmers. The research area was determined purposively. Determination of research respondents was carried out by snowball sampling with a total of 54 respondents. The research was conducted descriptively. Indicators of farmer group dynamics including farmer group objectives, task functions, group coaching and development, group unity, group atmosphere, group pressure, group effectiveness, and hidden intentions. The results showed that 56.5% of respondent understood the group's objectives, 60% of respondent replied that there was a clear division of tasks in the coffee farmer groups. The selection of administrators in the group structure is based on aggrement among member group. 70.2% of respondent farmers said that groups provide information about group activities. 77.7% of respondents said that groups invite and involve their members to participate in group activities based on the abilities and skills of the members. 80.2% of respondents said that the group has a strong sense of unity. 60% of farmers feel that the conflict and pressure that occurs in the group does not disturb the atmosphere within the group because it has been managed well. 58.6% of farmers think that there is no conflict and internal competition among members of the group. 69.1% of respondents think that the goals in the group are easy to understand. Keywords: Group dynamics, Coaching Pattern and Coffee Cluster